Rosmarinus officinalis essential oil as an effective antifungal and herbicidal agent - Ben Kaab, Sofiene; Rebey, Iness B.; Hanafi, Marwa; Berhal, Chadi; Fauconnier, Marie L.; De Clerck, Caroline; Ksouri, Riadh; Jijakli, Haissam (Spanish Journal of Agricultural Research, 2019)
In order to reduce the use of chemical pesticides, great interest has been focused on environment-friendly biological control agents and botanicals that preserve biodiversity. In this context, our study aimed to assess the antifungal and herbicidal activities of Rosmarinus officinalis essential oil (EO) to find an alternative to synthetic pesticides. The chemical composition of R. officinalis essential oil was determined by gaz chromatography-mass spectrometry analysis (GC-MS). Results showed that R. officinallis EO was rich in monoterpenes and the major constituents were 1,8-cineole (54.6%), camphor (12.27%) and α-pinene (7.09%). However, under laboratory conditions, two tests were carried out. The first one consisted on the study of EO antifungal activity using ELISA microplates and the second one consisted on evaluating the effect of EO on seedling growth of weeds. It was confirmed that this EO significantly inhibits spore germination of Fusarium oxysporum, Fusarium culmorum, Penicillium italicum and at 6 mM, the percentage of inhibition reached 100% on Fusarium oxysporum. Indeed, EO slows down seedling growth of Trifolium incarnatum, Silybum marianum, and Phalaris minor. In fact, EO at 5 mM completely inhibits seed germination. On the other hand, another experiment was carried out to evaluate the herbicidal activity by spraying EO on weeds. This showed that a novel herbicide formulation was set up for the first time to improve the activity of R. officinalis EO on post-emergence. Overall, R. officinalis EO can be suggested as a potential eco-friendly pesticide and suitable source of natural compounds potentially usable as natural pesticides.